The Concept of Criminal Law for Personnel of Narcotics Abuse - Dhian Artwitadibrata; Akhmad Khisni (Jurnal Daulat Hukum, 2020)
The purpose of this paper is to review and analyze the juridical review by the prosecutor in criminal procedural law. In this paper the writer uses the normative juridical method. In the conclusion of the discussion that in handling narcotics cases, especially offenders who are more emphasized as victims or addicts, judges in Indonesia can be said to rarely make legal breakthroughs that emphasize social values and humanity that live in society. Judges in Indonesia only see the criminal side in the Act regardless of the negative effects of the decision, the result is that imprisonment is only seen as providing a deterrent effect to the perpetrator of a criminal act. According to the Narcotics Law, victims of narcotics users are sentenced to imprisonment because drug users are classified as criminal offenders. This contradicts the legal theory of victimology. Several countries have proven that decriminalization policies have an effect on reducing narcotics abuse. The optimum model of punishment for victims of narcotics users is a process outside the legal process, in which all victims of narcotics users report themselves to be rehabilitated. Meanwhile, for those who did not report themselves, the police and / or BNN made arrests and were immediately escorted and handed over to the rehabilitation.